The enzymal substantiation of lymphotropic antibacterial therapy in an acute pancreatitis - I. D. Duzhyi; M. G. Kononenko; O. L. Sytnik; V. V. Shimko; O. V. Kravets; I. M. Medvedieva (Клінічна хірургія)
Objective. To study the impact of antibacterial therapy on level of proteolytic enzymes on example of the neutrophils elastase, and clinical course of an acute pancreatitis.